2020
DOI: 10.1249/mss.0000000000002471
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic Sequence Classification and the Relationship to Pitching Limb Torques

Abstract: Purpose The kinematic sequence (KS) during a baseball pitch provides insight into an athlete’s ability to efficiently transfer energy and develop segmental velocities, to assess the quality of body segment position and control. Study purposes were 1) to introduce the four-category Kinematic Sequence Classification System and 2) to compare elbow and shoulder torques and shoulder distraction force across the KS categories performed during the fastball pitch. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…The previously described Kinematics Sequence Classification groups the observed KSs to better understand the influences that altered sequences have on the pitcher's body. Each group is named relative to the first body segment that demonstrates peak angular velocity out-of-sequence from the targeted proximal-to-distal sequence (Scarborough et al, 2021 ). The groups described previously include: (1) the proximal-to-distal (PDS) group which also includes the closest to the ideal sequence where the forearm and the hand segments' peak angular velocities peak simultaneously, (2) the altered distal upper extremity (DUE) group, and (3) the altered proximal upper extremity (PUE) group and the altered pelvis/trunk (CORE) group (Scarborough et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The previously described Kinematics Sequence Classification groups the observed KSs to better understand the influences that altered sequences have on the pitcher's body. Each group is named relative to the first body segment that demonstrates peak angular velocity out-of-sequence from the targeted proximal-to-distal sequence (Scarborough et al, 2021 ). The groups described previously include: (1) the proximal-to-distal (PDS) group which also includes the closest to the ideal sequence where the forearm and the hand segments' peak angular velocities peak simultaneously, (2) the altered distal upper extremity (DUE) group, and (3) the altered proximal upper extremity (PUE) group and the altered pelvis/trunk (CORE) group (Scarborough et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Performance of this efficient transfer of segmental angular velocity is reported to reduce stress on musculoskeletal structures and thus the probability of injury while also maximizing ball velocity (Putnam, 1993 ; Seroyer et al, 2010 ; Chalmers et al, 2017 ; Scarborough et al, 2020 ). Recent investigations on a sample of fastball pitches performed by a group of high school, collegiate, and professional pitchers revealed that there are at least 17 distinct observable KS patterns (Scarborough et al, 2021 ). Out of the 17 observed patterns, none displayed the most efficient proximal-to-distal KS desired.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a mixed cohort of players ranging from high school (HS) to PRO, those who followed a proximal-to-distal sequence of segmental velocities demonstrated decreased elbow varus torque and shoulder internal rotation torque. 30,31 Additional studies have validated the importance of the temporal phases of the pitching motion. In collegiate and PRO pitchers, those who initiated trunk rotation before lead foot contact had significantly higher elbow varus torque compared with those who rotated after foot contact.…”
mentioning
confidence: 99%